2000
DOI: 10.1021/jf991002+
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-MS Study of the Flavonoid Glycoside Malonates of Red Clover (Trifolium pratense)

Abstract: High-performance liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) was applied to the analysis of the flavonoids and their glycoside malonates of the flowers and leaves of red clover (Trifolium pratense). Through LC-MS comparative studies on the plant extracts and their malonate-free extracts, approximately 20 flavonoid glycoside malonates were detected in the flower extract. Eight were identified as genistin 6' '-O-malonate (39), formononetin 7-O-beta-D-glucoside 6' '-O-malonate (40)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 23 publications
(44 reference statements)
8
103
0
Order By: Relevance
“…Peak F-6 had the same UV spectra and aglycone ion as peak F-5 (quercetin 3-O-glucoside), but its molecular ion is 86 amu larger than that of F5 and or 248 amu larger than that of its aglycone. Thus, F-6 was tentatively identified as quercetin 3-O-(6″-malonyl) glucoside (Cuyckems & Cleays, 2004;Lin et al, 2000). Similarly, peaks F-9 and F-10 were identified as kaempferol 3-O-(6″-malonyl)glucoside and kaempferol 3-O-(malonyl)glucoside.…”
Section: Identification Of Bean Flavonoidsmentioning
confidence: 97%
See 2 more Smart Citations
“…Peak F-6 had the same UV spectra and aglycone ion as peak F-5 (quercetin 3-O-glucoside), but its molecular ion is 86 amu larger than that of F5 and or 248 amu larger than that of its aglycone. Thus, F-6 was tentatively identified as quercetin 3-O-(6″-malonyl) glucoside (Cuyckems & Cleays, 2004;Lin et al, 2000). Similarly, peaks F-9 and F-10 were identified as kaempferol 3-O-(6″-malonyl)glucoside and kaempferol 3-O-(malonyl)glucoside.…”
Section: Identification Of Bean Flavonoidsmentioning
confidence: 97%
“…Based on the data presented in Table 2, the trace peaks A-4, A-8 and A-7 of small red beans were tentatively identified as pelargonodin 3,5-O,O-diglucoside, pelargonidin 3-O-(6″-malonyl)glucoside and cyandin 3-O-(6″ -malonyl) glucoside, respectively. The later two anthocyanins had molecular ions that were 248 amu larger than their aglycones and 86 amu larger than that of their glucosides; a typical pattern for flavonoid malonylglucosides (Cuyckems & Cleays, 2004;Lin et al, 2000).…”
Section: Identification Of Bean Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a two-dimensional SPE method, using Oasis HLB, RP 105 and Abselut sorbents in combination with an LC -ESI MS system, enabled the identification of fourteen isoflavone glycoside malonates in T. pratense [12]. Lin et al [13] used the same LC -ESI MS system and identified six isoflavone glucoside malonates in flowers and leaves of red clover. Extraction enhanced by sonication and followed by acid and basic hydrolysis was used by Delmonte and co-workers [14] to determine isoflavone levels in dietary supplements containing red clover.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that iridoid glycosides and flavonoids are two major components of L. rotata [3][4][5]. Many HPLC [6][7][8][9], CE [10][11][12][13][14], highperformance liquid chromatographic-mass spectrometric (HPLC-MS) [15][16][17], and gas chromatographic-mass spectrometric (GC-MS) [18,19] methods have been developed for the separation and analysis of iridoid glycosides and flavonoids. 8-O-acetylshanzhiside methylester, 6-O-acetylshanzhiside methylester, shanzhiside methylester, 8-deoxyshanzhiside, sesamoside, loganin, penstemoside, phlomiol, 7, 8-dehydropenstemoside, phloyoside I, phloyoside II, lamiophlomiside, phlorigidoside C, and seven other iridoid diglycosides have been isolated and reported as iridoid glycosides in the last 20 years [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%